Keragaman Jenis, Pola Tanam dan Produktivitas Sistem Agroforestri pada Beberapa Lanskap Pedesaan di Kabupaten Kutai Kartanegara - Pranoto, Hadi; Yuni, Irma (http://arl-faperta.ipb.ac.id/, 2025)
The rural landscape influences the level of diversity, cropping patterns and productivity of agroforestry systems. The aim of the research is to determine the diversity, cropping patterns and productivity of agroforestry systems in three rural landscapes in Kutai Kartanegara Regency, including Muara Jawa Ilir Village, Muara Jawa Tengah Village, and Muara Jawa Ulu Village. Data was obtained through field observations, interviews and literature study. Data analysis was carried out by analyzing the diversity in the landscape agroforestry, the patterns applied, and productivity is calculated based on the production value on a land and based on the selling price of a sample of land. The research results showed that the highest diversity was found in Muara Jawa Ilir Village and Muara Jawa Tengah Village, dominated by 12 types of fruit-producing stands. The components in Muara Jawa Ilir Village and Muara Jawa Tengah Village are 90% agrisilviculture and 10% agrosilvopasture, while in Muara Jawa Ulu Village it is 80% agrisilviculture, 10% silvopasture and 10% agro silvopasture. The pattern applied in Muara Jawa Ilir Village and Muara Jawa Ulu Village is 90% mixed pattern and 10% hedge pattern, while in Muara Jawa Tengah Village 100% uses mixed pattern. The highest productivity of the agroforestry system is in Muara Jawa Ulu Village with an average income of IDR. 5.819.383/year, and the lowest was in Muara Jawa Ilir Village, namely IDR. 5.012.318/year